Lipidic Nano-Sized Emulsomes Potentiates the Cytotoxic and Apoptotic Effects of Raloxifene Hydrochloride in MCF-7 Human Breast Cancer Cells: Factorial Analysis and In Vitro Anti-Tumor Activity Assessment - Hibah M. Aldawsari; Osama A. A. Ahmed; Nabil A. Alhakamy; Thikryat Neamatallah; Usama A. Fahmy; Shaimaa M. Badr-Eldin (Pharmaceutics, 2021)
Raloxifene hydrochloride (RLX), an antiosteoporotic agent, has been utilized for guarding against breast cancer and recently, for the disease management owing to its estrogen antagonist activity. Nevertheless, RLX exhibits poor bioavailability that could be attributed to reduced water solubility and first pass metabolism. To overcome these challenges, this study aimed at formulating and optimizing RLX emulsomes (RLX-EMLs) to enhance the drug antitumor activity. A 4131 factorial design was employed for assessing the effect of lipoid: solid lipid ratio and solid lipid type on the emulsomes characteristics. The anticancer potential of the optimized formulation and apoptotic parameters were assessed. Vesicle size, entrapment, and release efficiency were significantly influenced by both variables, while zeta potential was influenced by lipoid: solid lipid at p < 0.05. The optimal formulation exhibited vesicle size of 236 ± 8.6 nm, zeta potential of −18.6 ± 0.7 mV, drug entrapment of 98.9 ± 4.9%, and release efficiency of 42.7 ± 1.8%. MTT assay showed concentration-dependent inhibition of MCF-7 cells viability. In addition, cells treated with RLX-EMLs showed significant arrest at G2/M phase associated with significant increase in apoptotic and necrotic cells. The enhanced cytotoxic and anti-proliferative effect of RLX-EMLs relative to raw drug was authenticated through increased Bax/Bcl-2 ratio, caspase-9 activation and depletion of mitochondrial membrane potential.